2020
DOI: 10.1007/s11665-020-05117-w
|View full text |Cite
|
Sign up to set email alerts
|

Interface Characterization of Ni/Al Bimetallic Explosively Welded Plate Manufactured with Application of Exceptionally High Detonation Speed

Abstract: The investigation is dedicated to the detailed microstructure characterization of explosively welded clads, in which, exceptionally and for cognitive purposes, a very high detonation speed of about 2800 m/s was used to manufacture bimetallic aluminum-nickel plates. The study involves detailed microstructural characteristics of the bonded zone at micro and nano level, especially focused on the expanded melted regions consisted mostly of Al3Ni, Al3Ni2 and AlNi phases. In situ heating experiment in transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
3
9
0
1
Order By: Relevance
“…The applied detonation velocity of 2000 m/s was high enough to obtain continuous weld between Al and Ni plates ( Figure 3 a), the same as in the case of very high detonation velocity of 2800 m/s, reported previously in [ 40 ]. In both these cases, the asymmetric waves at the interface are observed.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The applied detonation velocity of 2000 m/s was high enough to obtain continuous weld between Al and Ni plates ( Figure 3 a), the same as in the case of very high detonation velocity of 2800 m/s, reported previously in [ 40 ]. In both these cases, the asymmetric waves at the interface are observed.…”
Section: Resultssupporting
confidence: 76%
“…Paul et al [ 11 ] have shown a series of microstructure images of Ti/Cu explosive welds, manufactured with the application of different V d in the range of 2000–3000 m/s and SOD increasing gradually by 1.5 mm in the range of 1.5–9.0 mm, where this relationship can be directly followed. Results presented here and in [ 40 ] show that the increase of V d and SOD causes an increase of waves’ amplitude and distance between their crests as in [ 11 ]. Guo et al [ 27 ] studied Ni/Al/Ni sandwiches manufactured by EXW with the detonation velocity of about 2100 m/s, indicating that the melted regions are more pronounced when the SOD is higher.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations